Hungarian Monitoring, 18 May 1990 . [Magyar rádiófigyelő], 1990. május 18 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USA reconsiders the activity of Radio Free Europe - Baker's talks in Moscow - Election news from Romania - Reunification treaty between the two Germanies - First session of the Russian Parliament Domestic Affairs: - President Bush meets Árpád Göncz in the White House - The aviation regiment of the Soviet Air Force leaves Debrecen - Compensation for the suspension of the construction works in Nagymaros - Police raids in Budapest against foreign currency smugglers Economy: - Headquarters of the Austrian state industry established in Budapest and Prague Külpolitika: - Az USA felülvizsgálja a SZER működését - Baker moszkvai tárgyalásai - Romániai választási hírek - Államszerződés a két Németország közt - Az orosz parlament első ülése Belpolitika: - Göncz Árpádot a Fehér Házban fogadja Bush elnök - A szovjet repülőezred elhagyja Debrecent - Kártérítési igény a nagymarosi építkezés leállítása miatt - Razziák Budapesten a valutázók ellen Gazdaság: - Az osztrák állami ipar vezérképviseletet létesít Budapesten és Prágában